2017
DOI: 10.18549/pharmpract.2017.01.853
|View full text |Cite
|
Sign up to set email alerts
|

Situation analysis of community pharmacy owners in Lebanon

Abstract: Objective:To evaluate the current community pharmacists’ interventions and job satisfaction, secondary to the alteration in the financial rewards.Methods:A cross-sectional study was carried out, using a proportionate random sample of Lebanese community pharmacy owners from all districts of Lebanon.Results:Out of 1618 distributed questionnaires, 1465 (90.5%) were collected back from pharmacy owners. Our study results showed that the monthly sales and profit decreased significantly in the last decade as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 21 publications
(31 reference statements)
2
32
2
Order By: Relevance
“…Moreover, recent findings showed that pharmacists don’t have enough time to counsel patients because of the decreased number of staff and the financial situation of community pharmacists in Lebanon. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent findings showed that pharmacists don’t have enough time to counsel patients because of the decreased number of staff and the financial situation of community pharmacists in Lebanon. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Despite the rigorous laws and regulations governing the pharmacy profession (medications only sold in pharmacies even non‐prescription ones, no advertisement allowed to both prescription and non‐prescription medications), thus theoretically preserving it from declining, the increasing numbers of pharmacy graduates seem to be the greatest threat of demise. While the number of pharmacists is increasing with respect to the rise in the population size, community pharmacists’ financial situation and related occupational satisfaction are degrading over time . This might be anticipated due to the increased competition and decreased quality of pharmaceutical care.…”
Section: Introductionmentioning
confidence: 99%
“…Community pharmacists are at the core of patient's education, especially education related to chronic diseases; they play an essential role in counseling, disease prevention, and management [20]. As the first place people visit for health consultation, the community pharmacy in Lebanon is the primary opportunity for COPD prevention and management; in fact, 90% of Lebanese pharmacists agreed that patients come to them first for counseling [21].…”
Section: Introductionmentioning
confidence: 99%